The Leeds Psychosexual Medicine Service: an NHS service for sexual dysfunction – review period 2. Issue 1 (2nd January 2016) - Trigwell, Peter; Waddington, Rachael; Yates, Andrew; Coburn, Sandra
ABSTRACT: National health service (NHS) psychosexual clinics are key providers of services for sexual problems in the UK. This report is the second in a series of three which describes the Leeds Psychosexual Medicine Service. It covers a three-year period (2009–2012), presenting information relating to 1085 patients referred to the service during that time. The majority of patients were in the age range 18–40 years and 54% were male. In 76% of cases the referral was from primary care and a broad range of sexual problems were referred. Only 31% of the total referrals were found to have completed all planned sessions of their treatment. Of those who did, 82.99% showed an improvement in their condition (42.71% major, 22.92% moderate, and 17.36% minor improvement), with no change in 15.97% and a deterioration in 1.04%. In common with the results of the first in this series of reports, our data suggest that brief therapy lasting six to eight sessions is beneficial in most patients and that, with minimisation of patient non-attendance, the brief interventions which we are finding to be effective could be made more so. This review series remains relevant in the current context of severe financial constraints and pressures on the NHS.